Pathophysiological deterioration and mortality of critically ill adult patients who underwent interhospital transportation - Carrillo, Marie Jesie; Cardoso de Sousa, Regina Marcia (Revista Chilena de Salud Pública, 2018)
Introduction: As inter-hospital transport of critically illl patients is associated with a risk of deterioration and death, it is important to identify factors that determine this risk to avoid harm to these individuals. Objective: To identify the predictive factors of pathophysiological deterioration during transfer and of death occurring during the first 24 hours after inter-hospital transport of critical care adult patients. Method: A prospective cohort study was performed in a sample of 3,629 patients transferred to a hospital Critical Care Unit (UPC, for initials in Spanish) by ambulances of the Emergency Medical Care Service (SAMU in Spanish) of the metropolitan area of Santiago, Chile. Deterioration of the transported patients was determined by calculating the Rapid Emergency Medicine Score (REMS) at the beginning and at the end of the transport. Multiple logistic regression was used to identify predictive models of death, pathophysiological deterioration, and pathophysiological deterioration followed by death. Results: The majority of transported patients were men (61.9%), and average REMS pre and post-transfer scores were 7.1 and 7.4, respectively. The majority of the patients were transferred from tertiary hospitals (77.7%), mainly due to a lack of UPC beds in those hospitals (54.7%). Pathophysiological deterioration occurred in 24.4% of the transported patients, and the prevalence of mortality post-translation was 4.5. Three predictive models were analyzed: for death (ROC: 0.78), for pathophysiological deterioration (ROC: 0.68) and for deterioration with death (ROC: 0.86). Conclusion: Identified protective factors include being transferred from a tertiary-level hospital and having an initially high SatO2 and elevated REMS. The use of hemodynamic support and manual respiratory ventilation were risk factors.